Do voters prefer educated candidates? How candidate education influences vote choice in congressional elections. (April 2023) - Arceneaux, Kevin; Vander Wielen, Ryan J.
Abstract: Previous research shows that democracies are more likely to produce educated politicians, but is this because voters prefer educated representatives or because of other features of the democratic process? Education may serve as a signal of candidate quality to voters or it may simply be associated with other factors, such as access to campaign funds, that help candidates win elections. We address this puzzle by analyzing head-to-head matches between candidates in US House elections from 2002 to 2012 along with a conjoint experiment. We find evidence that candidates with higher levels of education win more votes than candidates with lower levels of education, even after we account for standard indicators of candidate quality and campaign spending. This education premium not only garners more votes, but it also translates into higher probabilities of winning. The experimental results and sensitivity analyses show that it is unlikely that these results are explained by a hidden confound. The experiment also illuminates that the education premium flows from perceptions of candidate qualification and ability to pursue respondent interests.